Labour, human capital and economic development in Sabah - Kasim Mansur (Penerbit UMS, 2021)
This book highlights some contemporary issues related to Sabah's economic growth, including socio-economic, labour and human capital. These issues are linked to relevant economic and growth theory approaches. Critical issues on the challenges in the development and the way forward to realise government policies such as the Sa bah Development Corridor (SDC), the National Key Economic Area (NKEA) and the implementation of zakat to eradicate poverty will also be discussed. Economic development for Sabah is essential and is an ongoing effort to ensure that Sabah can compete in a gradually competitive economy. Implementing sound economic policies is vital in improving the social well-being and standard of living in the state. This book also explores socioeconomic issues involving various ethnic groups in Sa bah, especially improving human capital and infrastructure investment. The author identified that these elements are the key contributors and enablers to Sabah's economic growth. Thus, economic growth and development are consistent agendas to ensure future generations can live comfortably in a conducive economic environment. Hence, this book re-emphasises the importance of knowledge workers in preparing the Industrial Revolution 4.0. The author also recommends that Sabah's further economic development be attained through rigorous efforts from strong cooperation of state and federal government and firms, private sectors, industries, non-governmental organisations (NGOs) and the people. The development can be realised through investment and innovation. This book is significant to academics, students, policymakers, and community in increasing awareness of the importance of labour, human capital and economic development in Sabah. While adding to existing literature, this book can also be an additional reference about Sabah's key economic characteristics and labour market.